(untitled) - Waxler, Caroline (Hoboken, N.J., 2004)
A one-of-a-kind guide to investing in vice industries.Although vices such as alcohol, tobacco, and gambling may be deemed socially irresponsible, in the investment world, these stocks continue to dramatically outperform the S&P 500 in this depressed market. Stocking Up on Sin shows readers how to get in on this hot investment trend and make the most out of publicly traded companies that deal with "vice" products such as coffee, weapons, alcohol, and tobacco.
Keywords: Investments,Đầu tư; Moral and ethical aspects,Đạo đức và các khía cạnh đạo đức